Immediate effects of hamstring stretching alone or combined with ischemic compression of the masseter muscle on hamstrings extensibility, active mouth opening and pain in athletes with temporomandibular dysfunction. Issue 3 (July 2016) - Espejo-Antúnez, Luis; Castro-Valenzuela, Elisa; Ribeiro, Fernando; Albornoz-Cabello, Manuel; Silva, Anabela; Rodríguez-Mansilla, Juan
Summary: Objective: To assess the immediate effects of hamstrings stretching alone or combined with ischemic compression of the masseter muscle on hamstrings extensibility, active mouth opening and pain in athletes with temporomandibular dysfunction and hamstrings shortening. Methods: Forty-two participants were randomized to receive the stretching technique (n = 21) or the stretching plus the ischemic compression (n = 21). Outcome measures were: hamstrings extensibility, active mouth opening, pressure pain thresholds and pain intensity. Results: Both interventions improved significantly active mouth opening (group 1: 35.7 ± 6.7 to 39.1 ± 7.6 mm, p < 0.001; group 2: 34.0 ± 6.2 to 37.6 ± 5.6 mm, p < 0.001), active knee extension (group 1: 33.1 ± 8.5 to 40.8 ± 8.2°, p < 0.001; group 2: 28.9 ± 6.5 to 35.5 ± 6.4°, p < 0.001) and pain. No significant differences were found between interventions. Conclusion: Hamstrings stretching induced an acute improvement in hamstrings extensibility, active mouth opening and pain. Moreover, the addition of ischemic compression did not induce further improvements on the assessed parameters.